2007
DOI: 10.1002/app.26571
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight studies of the γ‐irradiation degradation of poly(methyl methacrylate) doped with poly(p‐sulfanilamide)

Abstract: The protection of some poly(methyl methacrylate) (PMMA) samples against c rays was investigated in the absence and presence of poly(p-sulfanilamide). Pure PMMA (without additives) and PMMA-poly(p-sulfanilamide) blend samples were irradiated with c rays for different exposure doses (5,15,25,35, 50, 75, and 100 kGy). The viscosity-average molecular weights were determined and thin-layer chromatography measurements were carried out after each irradiation dose. The maximum protection against c rays was found when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Height initially increased when the electron fluence also rose due to the elastic property of a polymer that causes the wrinkle height to increase with increasing applied compressive stress. However, the molecular weight of irradiated PMMA decreases exponentially with increasing electron irradiation fluence, , signifying that the scission rate of PMMA becomes insignificantly small past a certain dose. Figure strongly supports this fact as it shows that the glass-transition temperature of PMMA and the received dose also have a closely inversely exponential relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Height initially increased when the electron fluence also rose due to the elastic property of a polymer that causes the wrinkle height to increase with increasing applied compressive stress. However, the molecular weight of irradiated PMMA decreases exponentially with increasing electron irradiation fluence, , signifying that the scission rate of PMMA becomes insignificantly small past a certain dose. Figure strongly supports this fact as it shows that the glass-transition temperature of PMMA and the received dose also have a closely inversely exponential relationship.…”
Section: Resultsmentioning
confidence: 99%
“…As revealed, pure PMMA showed a 68.2% heterotacticity which indicated that it is nearly amorphous [26]. In the presence of cadmium and mercury complexes, the tacticity of all samples was signi cantly improved as shown in Table 2, reducing in turn the amorphous region that is the most susceptible for all physical and chemical interactions and degradation compared to the crystalline region [45]. The overall results clearly indicate the direct outcome of the carbazone complexes role as catalyst and regulator during the emulsion polymerization of MMA which enrich the prepared polymers with an explicated effectiveness against radiation.…”
Section: G-ray Degradation and Protection E Ciencymentioning
confidence: 91%